Prognostic value of serum PIIINP, MMP1 and TIMP1 levels in hypertensive patients: a community‐based prospective cohort study. (13th July 2012) - Agrinier, Nelly; Thilly, Nathalie; Boivin, Jean‐Marc; Dousset, Brigitte; Alla, François; Zannad, Faiez
Abstract The purpose of this study was to examine the prognostic value of serum ECM biomarkers in hypertensive patients with no history of cardiovascular events. In a community‐based cohort study of 125 hypertensive patients free of cardiovascular events, we collected clinical data and blood samples to assess serum levels of amino‐terminal propeptide of type III procollagen (PIIINP), matrix metalloproteinase type 1(MMP1) and tissue inhibitor of MMPs type 1(TIMP1). Left ventricular hypertrophy (LVH) was assessed using the ECG Cornell product. Patients were followed up for death or cardiovascular hospitalisation. We used Cox regression models to assess the prognostic value of ECM biomarkers. The sample included 60.8% women; the mean (±SD) age was 62.9 (±11.4) years. Patients were followed up for a median of 5.5 years, during which 23 events (five deaths) occurred. PIIINP (3.2 ± 1.0 vs. 2.6 ± 0.8 μg/L, P = 0.001) and TIMP1 (886 ± 168 vs. 751 ± 202 μg/L, P < 0.001) levels were higher in the presence of LVH than with no LVH. Basal MMP1 serum levels were significantly associated with CV events (MMP1: HR, 1.06; 95%CI [1.02–1.09]). Adjusting for confounders did not modify this result. Cardiac fibrosis, as assessed with serum ECM biomarkers, might develop early in hypertensive patients and is predictive of cardiovascular events or death.